HISTOLOGICAL ANALYSIS OF WISTAR RATS SCIATIC NERVES SUBJECTED TO COMPRESSION AND TREATED WITH LOW LEVEL LASER THERAPY AND NEURAL MOBILIZATION - Antunes, Juliana Sobral; Karvat, Jhenifer; Bernardino, Giovanni Ribeiro; Kakihata, Camila Mayumi Martin; Bertolini, Gladson Ricardo Flor; Brancalhão, Rose Meire Costa; Ribeiro, Lucinéia de Fátima Chasko; Aragão, Fernando Amâncio (Malang Neurology Journal, 2019)
Background: The physical therapy resources, as Low-Level Laser Therapy (LLLT) and neural mobilization are usually used with regenerative purpose and for the relief of symptoms for peripheral nerve injury. However, there is a lack of consensus on its effects as well as its association. Objective: Evaluate the influence of low-level laser therapy (LLLT) associated with neural mobilization (NM) on nerve regeneration of female Wistar rats subjected to sciatic compression. Methods: Twenty four Wistar rats were divided into: G1 (Placebo), G2 (NM), G3 (LLLT) and G4 (NM+LLLT), all animals were subject to compression of the right sciatic nerve. The treatment occurred on the 3rd, 5th, 7th, 10th, 12th and 14th postoperative day (PO). On the 17th PO the animals were euthanized. Histological and morphometric analysis of the right (compression) and the left (control) sciatic nerve were performed.Results: In the morphometric analysis no significant differences between groups, but differences among sides were found. Histological analysis revealed the presence of inflammatory infiltrate and disruption of nerve fibers in the right sciatic nerves.Conclusion: Both techniques used (LLLT and neural mobilization), isolated and associated, on the parameters proposed, were not effective to accelerate the process of nerve regeneration.